PEMBUATAN AUDIT JUDGEMENT: SELF-EFFICACY, TEKANAN KETAATAN, KOMPLEKSITAS TUGAS DAN PENGALAMAN AUDITOR - Rahma, Yusro; Safrida, Melisa (Department of Accounting-Faculty of Economic and Business (FEB), 2024)
This study aimed to test hypothesis and produce empirical evidence regarding the influence of self-efficacy, obedience pressure, task complexity, and auditor experience on audit judgement making. The data research were gathered using a questionnaires distributed to 100 external auditors working at Public Accounting Firms registered in the Big 10. The results toward the data showed that self-efficacy have a negative effect on making audit judgements, obedience pressure have a negative effect on making audit judgements, task complexity have a positive effect on making audit judgements, and auditor experience have a positive effect on making audits judgement.